Analytical Study to Estimate Market waste of Apple Crop in The Green Mountain Region - Ifhima, Joma A.; Tolba, Adly S.; Omar, Soad S. (Al-Mukhtar Journal of Sciences, 2007)
The study focused on the main factors affecting the increase in the market waste of apple crop, the market waste of the study crop reached about 6% of total production per- hectar , the reducing of these waste will must increase the producer income with 302 Dinars , the study deals with estimating the marketing losses at the farm and retailer market levels of the apple crop ,the study concerned with the quantitative analysis of the different factors affecting market waste ratio using multi-regression analysis, The study shows that crop quantity , average farm price has a statistically significant negative relationship market waste ratio of apple, the study presents some of recommendation to help in reducing the losses of the studied crop.